Tanggung Jawab Pemberi Waralaba Terhadap Penerima Waralaba Atas Merek Usaha Waralaba Yang Tidak Terdaftar - Sahla, Raja Nabilla Marshanda; Lestari, Rika; Putra, Setia (PATTIMURA Legal Journal, 2024)
Introduction: The franchisor did not register the business brand with the Directorate General of Intellectual Propertymso that the franchisor could not make a Franchise Prospectus and could not apply for a Franchise Registration Certificate. Purposes of the Research: The purpose of this research is to find out how the legal consequences for franchisees for unregistered franchise business marks and to find out the responsibilities of franchisors to franchisees for unregistered franchise business marks in Pekanbaru City. Methods of the Research: The type of research used is sociological legal research that wants to see the correlation between law and society, so as to reveal the effectiveness of the application of law in society. Results of the Research: This study found that the legal consequences of franchises that do not register their trademarks will result in a franchise agreement made by the franchisor and franchisee will be null and void because it does not meet the valid requirements of the agreement, namely the halal causa. The responsibility given by the franchisor to franchisees who have suffered losses is compensation and and immediately register their business brand and apply for a Franchise Registration Certificate to the authorized agency.